Research Progress on the Role of Regulatory T Cell in Tumor Microenvironment in the Treatment of Breast Cancer - Liu, Jianyu; Wang, Xueying; Deng, Yuhan; Yu, Xin; Wang, Hongbin; Li, Zhigao (Frontiers in Oncology, 2021)
The tumor microenvironment (TME) is a complex ecosystem comprised of both cancer cells, stromal cells and immune cells. Analysis of the composition of TME is essential to assess the prognosis of patients with Breast cancer (BC) and the efficacy of different regimes. Treg plays a crucial role in the microenvironment of breast cancer subtypes, and its function contributes to the development and progression of BC by suppressing anti-tumor immunity directly or indirectly through multiple mechanisms. In addition, conventional treatments such as anthracycline-based neoadjuvant chemotherapy and neo-therapies such as immune-checkpoint blockades (ICBs) have a significant impact on the absence of Tregs in BC TME, thus gaining additional anti-tumor effect to some extent. Strikingly, Treg in BC TME revealed the predicted efficacy of some therapeutic strategies. All these results suggest that we can manipulate the abundance of Treg to achieve the ultimate effect of both conventional and novel treatments. In this review, we discuss new insights into the characteristics of Treg in BC TME, the impact of different regiments on Treg, and the possibilities of Treg as a predictive marker of efficacy for certain treatments.